All-solid state ion-selective carbon black-modified printed electrode for sodium detection in sweat. (20th October 2021) - Mazzaracchio, Vincenzo; Serani, Aristi; Fiore, Luca; Moscone, Danila; Arduini, Fabiana
Abstract: The synergic combination of printed electronics and printed electrochemical sensors has recently emerged as a new route for developing smart chemical wearable devices applied to sweat monitoring. Sodium ion is one of electrolytes monitored in sweat to evaluate sweating level for electrolyte replacement recommendations. Herein, we report the development of new designed screen-printed electrodes, in which working electrode has been easily modified by drop-casting with the nanomaterial carbon black and a selective membrane cocktail, and the reference electrode with a polyvinyl butyral-based membrane. Once optimised all conditions, the screen-printed electrochemical sensor demonstrated no aqueous layer formation between working electrode and selective membrane, long-term potential stability, good shelf life, and resistance to interferences from oxygen and light. The carbon black-based sensor allowed for the detection of sodium ions in range 10 -4 M e 1 M with a slope of 58 ± 3 mV/decade and a detection limit of 63 µM. The applicability for sweat analysis was evaluated by analysing three sweat samples collecting during running activity, obtaining concentrations of 44 ± 4 mM, 55 ± 6 mM, and 47 ± 3 mM, values in agreements with sodium ions content in healthy people, as well as using artificial sweat with recovery values of 90 ± 3%, 94 ± 2%, and 94 ± 5%.